221 Adhesive spinal arachnoiditis following subarachnoid haemorrhage mimicking a multiple sclerosis relapse. Issue 6 (27th May 2022) - Farag, Mena; Younus, Osman; Hampton, Timothy; Walsh, Daniel; Silber, Eli
Abstract : We present a case of adhesive spinal arachnoiditis, as a complication of a fall with traumatic subarach- noid haemorrhage, in a patient with progressive multiple sclerosis (MS). A 68 year-old woman with MS and spasticity, on Baclofen, Pregabalin and Nabiximols, was admitted following a fall. CT scanning demonstrated traumatic subarachnoid haemorrhage. She was admitted to the ITU initially and managed conservatively. Four months later, while undergoing inpatient rehabilitation, her condition deteriorated over six weeks with worsening paraparesis, neurogenic bladder and bowel dys- function with a C5–6 sensory level. She received steroids and underwent MRI of her neuroaxis. Imaging of her brain showed unchanged demyelinating lesions. Spinal imaging identified distortion with considerable T2 signal change in the cervical and thoracic regions, extending from the C5/6 to the T8/9 level, radiologi- cally consistent with a syrinx and myelopathy. It was felt her deterioration was not due to demyelination but secondary to cervicothoracic adhesions ventral to the cord as sequelae of cerebral haemorrhage. Following neurosurgical review, the patient underwent C4-T1 laminoplasty, adhesionolysis and expansion duraplasty with histopathology showing calcified connective tissue but the clinical outcome has thus far been poor. It is important to consider all the causes of deterioration in patients with progressive MS. menafarag@doctors.org.uk